FIRST CHECKLIST OF LADYBIRDS (COLEOPTERA: COCCINELLIDAE) OF CROATIA ALONG WITH NEW FAUNISTICAL RECORDS (Acta Entomologica Serbica, 2012)
The ladybird fauna of Croatia is insufficiently known. New ladybird records collected during the last 4 years across Croatia are given. The first preliminary checklist of ladybirds of Croatia consisting of 78 species is presented